SUPPRESSOR OF PHYTOCHROME B-4 #3 reduces the expression of PIF-activated genes and increases expression of growth repressors to regulate hypocotyl elongation in short days - Caitlin N. Jacques; David S. Favero; Ayako Kawamura; Takamasa Suzuki; Keiko Sugimoto; Michael M. Neff (BMC Plant Biology, 2022)
Abstract SUPPRESSOR OF PHYTOCHROME B-4 #3 (SOB3) is a member of the AT-HOOK MOTIF CONTAINING NUCLEAR LOCALIZED (AHL) family of transcription factors that are involved in light-mediated growth in Arabidopsis thaliana, affecting processes such as hypocotyl elongation. The majority of the research on the AHLs has been conducted in continuous light. However, there are unique molecular events that promote growth in short days (SD) compared to constant light conditions. Therefore, we investigated how AHLs affect hypocotyl elongation in SD. Firstly, we observed that AHLs inhibit hypocotyl growth in SD, similar to their effect in constant light. Next, we identified AHL-regulated genes in SD-grown seedlings by performing RNA-seq in two sob3 mutants at different time points. Our transcriptomic data indicate that PHYTOCHROME INTERACTING FACTORS (PIFs) 4, 5, 7, and 8 along with PIF-target genes are repressed by SOB3 and/or other AHLs. We also identified PIF target genes that are repressed and have not been previously described as AHL-regulated, including PRE1, PIL1, HFR1, CDF5, and XTR7. Interestingly, our RNA-seq data also suggest that AHLs activate the expression of growth repressors to control hypocotyl elongation, such as HY5 and IAA17. Notably, many growth-regulating and other genes identified from the RNA-seq experiment were differentially regulated between these two sob3 mutants at the time points tested. Surprisingly, our ChIP-seq data suggest that SOB3 mostly binds to similar genes throughout the day. Collectively, these data suggest that AHLs affect gene expression in a time point-specific manner irrespective of changes in binding to DNA throughout SD.